Cultural economics - Hellmanzik, Christiane (Newcastle upon Tyne : Agenda Publishing, 2020)
Cultural Economics investigates and analyses the contribution to and role of the creative industries and their products and services in the overall economy. From the performance arts to television, from the internet to paintings and publishing, the creative industries can be goods or services that are both public and private, protected by copyright, consumed, created, auctioned and susceptible to fashion and technological development. In this fascinating introduction to the field, Christiane Hellmanzik unpacks the complexity of the issues at stake and through the careful use of case studies illuminates the challenges that the creative industries present for economic analysis. Topics covered include the demand for culture, investment, the superstar theory and the impact of globalization and the internet on markets and industrial models.
1 Introducing cultural economics -- 2 Markets, prices and agents -- 3 Society and culture: public provision and institutional aspects -- 4 Demand for culture -- 5 Artists, superstars and creativity -- 6 Quality in the arts and culture -- 7 The organization of cultural industries -- 8 The internet's impact on cultural sectors -- 9 Globalization's impact on cultural sectors -- 10 Conclusion.
Includes bibliographical references and index.
Keywords: Cultural industries -- Economic aspects; Arts -- Economic aspects